From Aspiring to 'Paradise' : the South Island myth and its enemies : a critical and creative investigation into the deconstruction of Aotearoa's Lakes District : presented in fulfilment of the requirements for the degree of Masters in Creative Writing at Massey University, Palmerston North, New Zealand - Wilson, Annabel (Massey University, 2014)
Poetry and film are artistic modes for representing, interpreting and evaluating our environment. Aotearoa’s poets have distilled the meanings we place on ‘places of the heart’ since the first oral histories and lyrics were composed. Kiwi filmmakers have also fixed their gaze on places layered with cultural significance, selecting Edens at various stages of the Fall as settings for their protagonists to mess about in. With New Zealand’s unique position as the last place on earth to be populated, the human response to this landscape is a significant aspect of the nation’s psyche, and the relationship between people and place remains an enduring motif in local writing and cinema. My research stems from an exploration of the poetic and on-screen representations of the Central Otago region as a cultural landscape generated by a variety of spectators. This paper takes an excursion into the high country of Te Wai Pounamu to see how two key places have been sighted in terms of the South Island myth. The first place to be framed is deep in the Matukituki valley. Here, the gaze of the nationalist era is epitomised by the ill-fated Aspiring film project masterminded by Brian Brake and scripted by James K. Baxter. The antithesis of their gaze can be seen in the ‘Paradise’ of Jane Campion’s post-feminist television mini-series Top of the Lake (2013). My interest is in the swing from Brake and Baxter’s romanticizing of Aotearoa’s ‘Lakes District’ to Campion’s brutalizing of it. How has the mythical South Island landscape been established and then fractured by these artists? These issues are also explored in my creative component, which draws upon my critical report in order to devise my own response to the South Island myth through a fictionalized journal / scrapbook entitled ‘Aspiring Daybook’.
Keywords: South Island; Motion pictures; Films; Lakes; Southern Lakes; Central Otago; Brian Brake; Jane Campion; James K Baxter; Creative writing; Fiction; Poetry; New Zealand; Aotearoa; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Film